Education as an Aspiration for Girls of Turkish Muslim Origin in Germany - Güner, Pinar Burcu (ETHICS IN PROGRESS, 2019)
In order to find the inequalities in the life of socially vulnerable Turkish origin girls; the present research conceptualized how ethnicity and migration background deprive or enhance capabilities (opportunities) of the 2nd, 3rd and 4th generation girls with a Turkish origin living in Germany. Data for research were collected in consultation with colleagues working in the field of youth and education in the Federal State of North Rheine Westphalia. The participants were girls between the ages of 13 and 21 years residing in North Rhine Westphalia`s (NRW) socio-economically vulnerable areas.